Analisa Manajemen Strategik Bisnis Mengenai Pt Indofood Sukses Makmur Tbk - Delvian Yosuky; Ricky Ricky; TioSaniaRachmi; Felix Felix (Serat Acitya, 2022)
PT Indofood Sukses Makmur Tbk is a company engaged in the food sector, located in Jakarta. The company was founded on August 14, 1990 under the name PT Panganjaya Intikusuma, and changed its name to Indofood Sukses Makmur on February 5, 1994. The company exports its food ingredients to Asia, Australia and Europe. This research will review the strategic management of a company, namely PT Indofood Sukses Makmur Tbk. In this study the authors used qualitative method techniques with a descriptive qualitative method approach. This study shows that PT Indofood Sukses Makmur Tbk carries out strategic management by promoting it on various platforms such as Instagram and TV shows. Then another management strategy is to continue to innovate to produce new products that can attract the attention of consumers and have added value.